Targeting MYOF suppresses pancreatic ductal adenocarcinoma progression by inhibiting ILF3-LCN2 signaling through disrupting OTUB1-mediated deubiquitination of ILF3 - Zhihui Li; Jianlei Zhang; Jiang Yin; Wen Ma; Hongfan Liao; Lv Ling; Qingfeng Zou; Yabing Cao; Ying Song; Guopei Zheng; Xiaoye Hu; Guohua Yang; et al. (Redox Biology)
Pancreatic ductal adenocarcinoma (PDAC) is still a highly aggressive and fatal disease. The molecular mechanisms for PDAC progression are still not fully understood. Here, we demonstrated the overexpression of MYOF in PDAC in multiple sample sets, which is significantly associated with poor outcome of PDAC patients. MYOF knockout suppresses PDAC progression in vitro and in vivo. MYOF knockout exerts its effects by promoting ferroptosis via downregulating LCN2 expression. Ectopic LCN2 expression overcame the effects of MYOF knockout in PDAC cells. Mechanistically, MYOF respectively recruits OTUB1 and ILF3 to enhance their interaction and relieves ILF3 protein ubiquitination and degradtion. MYOF maintains ILF3 protein stability, thereby enhances ILF3 interacting with and improving LCN2 mRNA stability. Moreover, we screened and identified natural compound Picroside II potentially targets MYOF to suppress PDAC progression. These findings uncover the biological roles and mechanisms of MYOF and preliminarily indicate the potential of targeting MYOF in PDAC progression, highlighting a novel therapeutic strategy for PDAC.